ANALISA COOLING SISTEM GE FRAME 9 PLTG SICANANG 120MW - Gaos, Yogi Sirodz; Widiawati, Candra Damis (Universitas Ibn Khaldun Bogor, 2016)
Power plant is an industrial facility for the generation of electric power. Mechanical power is produced by a heat engine that transforms thermal energy, often from combustion of a fuel, into rotational energy for generator, than produces electric power. On all the power plant is operated in high temperature and high pressure, so it needed cooling system to prevent from over heating, if not the power plant system will be damaged. PLTG Sicanang produced 120MW electric power; the cooling systems consist of generator cooler and turbin cooler. Design input data was temperature inlet and outlet water, volumerate water, and ambient temperature. Design performance of generator cooler 1) capacity 2450 kW 2) water inlet 46.5oC and water outlet 40oC 3) water volume flow 330 m3/h 4) air volume flow 312m3/s. Design performance of turbin cooler 1) capacity 1570 kW 2) water inlet 56.3oC dan water outlet 46.5oC 3) water volume flow 140 m3/h 4) air volume flow 312m3/s. The actual performance for 50 MW load 1) generator cooler; water inlet 43oC, water outlet 40oC, water volumerate 330 m3/h, air volumerate 182m3/s 2)turbin cooler water inlet 47oC, water volumerate 140 m3/h, air volumerate 182m3/s. 100 MW load 1) generator cooler; water inlet 45oC, water outlet 40oC, water volumerate 330 m3/h, air volumerate 208m3/s 2)turbin cooler water inlet49oC, water volumerate 140 m3/h, air volumerate 208m3/s. The generator cooler has been designed with reverse surface 25% which was capable to cooling heat 3066 kW, where as the turbin generator has been designed with reverse surface 17% which was capable to cooling heat 1850 kW. The reverse surface was designed to anticipate hinger ambient temperature and over load.